2019
DOI: 10.1186/s40360-019-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of severe adverse effects following community-based ivermectin treatment in the Democratic Republic of Congo

Abstract: Background The progress of mass, community-directed, treatment with ivermectin (CDTI) for onchocerciasis control was disrupted by severe adverse effects (SAE) in the Democratic Republic of Congo (DRC). The study aimed at determining the frequency of post-CDTI SAE as well as factors associated with the occurrence of SAE. Methods Our retrospective study relied on SAE collection cards, as archived by the DRC Ministry of Health, and compiled for people who benefited from iv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…ALB is a benzimidazole derivative with a great absorption after oral administration and a wide spectrum of activity. 37 There are currently no studies that suggest the use of albendazole as an alternative regimen for loiasis, and a short regimen with ALB has been demonstrated to have little effect on microfilaraemia. 38 Its role is accepted by the CDC if a blood tests shows > 8,000 microfilaria/mL, at a dosage of 200 mg twice daily for 21 days to reduce the Loa loa microfilariemia (LLM) and to avoid the neurological adverse effects of DEC.…”
Section: Treatmentmentioning
confidence: 99%
“…ALB is a benzimidazole derivative with a great absorption after oral administration and a wide spectrum of activity. 37 There are currently no studies that suggest the use of albendazole as an alternative regimen for loiasis, and a short regimen with ALB has been demonstrated to have little effect on microfilaraemia. 38 Its role is accepted by the CDC if a blood tests shows > 8,000 microfilaria/mL, at a dosage of 200 mg twice daily for 21 days to reduce the Loa loa microfilariemia (LLM) and to avoid the neurological adverse effects of DEC.…”
Section: Treatmentmentioning
confidence: 99%
“…At very high doses, Ivermectin results in CNS toxicity in farm animals that manifests as lethargy, ataxia, mydriasis, tremors, and eventually death 19 . Most of the time, mazzotti-like reactions to dying microfilariae develop in infected humans injected with Ivermectin due to hypertensives reaction to dead microfilariae.…”
Section: Ivermectinmentioning
confidence: 99%
“…For example, a retrospective study depicted the occurrence of severe neurological and non-neurological adverse effects, including coma, arthralgia, severe headaches, and palpebral subconjunctival hemorrhages, after MDA of 2 in onchocerciasis- and L. loa-coendemic areas in Congo . To check whether 2 may express CNS toxicity because of its affinity toward GABA-Cls, a study was conducted in Cameroon in which four individuals coinfected with Onchocerca volvulus and L.…”
Section: Adverse Effects Of Ivermectin and Resistance Developmentmentioning
confidence: 99%
“…For example, a retrospective study depicted the occurrence of severe neurological and nonneurological adverse effects, including coma, arthralgia, severe headaches, and palpebral subconjunctival hemorrhages, after MDA of 2 in onchocerciasis-and L. loa-coendemic areas in Congo. 120 To check whether 2 may express CNS toxicity because of its affinity toward GABA-Cls, 121 a study was conducted in Cameroon 122 in which four individuals coinfected with Onchocerca volvulus and L. loa who displayed adverse events after MDA of 2 were assessed for plausible mutations of the MDR1 gene. 123,124 However, the absence of any loss-of-function mutations in P-glycoproteins (P-gps) suggested that the occurrence of adverse effects post-treatment of 2 may be linked to the accumulation of L. loa microfilaria in cerebrospinal fluid.…”
Section: Adverse Effects Of Ivermectin Andmentioning
confidence: 99%